Buzz: Peek-a-Boo Baby - Waring; Zoe (Great Britain Pat-a-Cake, 2021)
Young children learn best through interactive play and Peek-a-Boo Baby: Buzz helps parents and carers with this as they share this book with their baby sitting on their lap. Simple questions and adorable pictures of a cute fawn, bunny, lamb, chick and bee hiding under the flaps will have babies squealing with delight as they play, point, laugh, say hello and play peek-a-boo!